2010
DOI: 10.1186/1478-811x-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Human uterine leiomyoma-derived fibroblasts stimulate uterine leiomyoma cell proliferation and collagen type I production, and activate RTKs and TGF beta receptor signaling in coculture

Abstract: BackgroundUterine leiomyomas (fibroids) are benign smooth muscle tumors that often contain an excessive extracellular matrix (ECM). In the present study, we investigated the interactions between human uterine leiomyoma (UtLM) cells and uterine leiomyoma-derived fibroblasts (FB), and their importance in cell growth and ECM protein production using a coculture system.ResultsWe found enhanced cell proliferation, and elevated levels of ECM collagen type I and insulin-like growth factor-binding protein-3 after cocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 44 publications
1
49
0
Order By: Relevance
“…Fibroblasts are an integral cellular component of human uterine fibroids and myometrium (Koumas et al 2001, Zaitseva et al 2007, Moore et al 2010, HoldsworthCarson et al 2014. Although fibroids are clonal, significant cellular heterogeneity exists (HoldsworthCarson et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibroblasts are an integral cellular component of human uterine fibroids and myometrium (Koumas et al 2001, Zaitseva et al 2007, Moore et al 2010, HoldsworthCarson et al 2014. Although fibroids are clonal, significant cellular heterogeneity exists (HoldsworthCarson et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance to this investigation, it is interesting to note that genes associated with steroid hormone regulation, the TGFB pathway and genes involved in the RA pathway make up a significant portion of genes that are differentially expressed in fibroid tissue compared with myometrium (refer to Table 1 for a brief summary; Sadan et al 1987, Dou et al 1996, Tsibris et al 2002, Skubitz & Skubitz 2003, Weston et al 2003, Shozu et al 2004, Arslan et al 2005, Leppert et al 2006, Zaitseva et al 2006, Roth et al 2007, Litovkin et al 2008, Lee et al 2010, Moore et al 2010, Davis et al 2013, Yin et al 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They generally grow in a spherical shape and, on the macroscopic scale, the cells appear to be distributed uniformly throughout. In addition to the smooth muscle component, they also possess a significant extracellular matrix consisting of fibroblasts [26]. They are therefore highly fibrous with the collagen fibrils randomly oriented, a characteristic different from the adjacent myometrium in which the collagen fibrils are aligned in an orderly fashion [20,30].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of myomas, the presence of oestrogen and progesterone up-regulates expression of a plethora of growth factors both within myocytes and fibroblasts, enhancing cell proliferation and collagen deposit [26], while at the same time the change in homeostasis in myomas accompanied by altered mechanical stresses, suggests the interplay between the chemical and mechanical effects and the role of stress in cell growth and fibroid development [20]. In vitro studies on tumour spheroids have also demonstrated resistance to tumour growth as a result of stress accumulated both within the tumour as well as in the surrounding medium.…”
Section: Introductionmentioning
confidence: 99%